2000
DOI: 10.1177/014572170002600413
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Factors That Affect Glycemic Control in College Students With Type 1 Diabetes

Abstract: Despite the perception that diabetes management was more difficult in college, metabolic control was maintained during college, possibly due to a more intensive treatment approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(82 citation statements)
references
References 14 publications
5
77
0
Order By: Relevance
“…In a qualitative study of young adults living with T1D, 71% reported that diabetes was more difficult to manage in college than in high school [1]. A similar study of urban youth with T1D conducted by Gee and colleagues found that challenges in establishing independence as a young adult were similar to those without a chronic condition, but coping with the management of diabetes magnified the difficulties of emerging adulthood and generally resulted in poor diabetes management [3].…”
Section: Background and Rationalementioning
confidence: 99%
See 2 more Smart Citations
“…In a qualitative study of young adults living with T1D, 71% reported that diabetes was more difficult to manage in college than in high school [1]. A similar study of urban youth with T1D conducted by Gee and colleagues found that challenges in establishing independence as a young adult were similar to those without a chronic condition, but coping with the management of diabetes magnified the difficulties of emerging adulthood and generally resulted in poor diabetes management [3].…”
Section: Background and Rationalementioning
confidence: 99%
“…The presence of a chronic condition such as type 1 diabetes (T1D) can exacerbate the complexities of this period of emerging adulthood by placing additional responsibilities on young adults as they adjust to a new environment and cope with new life situations [1]. Additionally, health care providers (HCPs) may face challenges assisting older adolescents and young adults transitioning from pediatric to adult clinical care due to gaps in patient healthcare utilization among emerging adults with diabetes.…”
Section: Background and Rationalementioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Ramchandani N et al commonly reported barriers to diabetes control included diet and irregular schedules. 12 This highlights the importance of diet control right from the stage of impaired glucose tolerance which is a risk factor in the occurrence and progress of diabetes.…”
Section: Dietmentioning
confidence: 99%
“…Targeting postprandial hyperglycemia is important in order to improve HbA1c levels and this has also been recently highlighted by the International Diabetes Federation guidelines (84,85). In everyday life the control of postprandial hyperglycemia poses even more challenges due to variations in dietary intake and physical exercise or insulin dosage and timing changes (patients may modify the timing of insulin administration in the sense of dosing immediately before or even after meals in order to fit their lifestyle / daily activity requirements) (86). In addition, lack of predictable insulin response may occur with insulin analogues because their absorption can be affected by various factors such as: mechanics of injection, the injection site, and metabolic factors, similar to regular human insulin (87).…”
Section: Insulinmentioning
confidence: 99%